History and Methods of the Everglades Soil Testing Laboratory - J. Mabry McCray; Ronald W. Rice (EDIS)
This publication provides a history of the University of Florida Everglades Soil Testing Laboratory (EvSTL), current analytical methods, and information about fertilizer recommendations made by the laboratory. Written by J. Mabry McCray and Ronald W. Rice, and published by the UF/IFAS Agronomy Department, October 2023.